A extensão universitária como um dos parâmetros de avaliação da universidade - Rodrigues, Marilúcia de Menezes (Educação e Filosofia, 2008)
Abstract: This work analyses the extension programme evaluation that has been carry out since 1993 in foruns of the Pró-reitors for extension programme of the Brazilian public universities. At the present time, the evaluation of the extension programme is a challenge for the institution in the sence that principles shoud be established to guide the process. The forum considers that the inclusion of extension programmes, as a parameter for evolvation of universities, implies that this activities part of the academic work, which is to be understood as an organic and continuous process. From this stand point, extension programme turns to be understood as a educative, cultural, technical cientific process, articulating, articulating teaching a research in a integrated way and, also guarantying the relationship that promotes changes between university and society. Keywords: University; Extension; Assessment. Resumo: O trabalho analisa a avaliação da extensão como parte das discussões dos Fóruns de Pró-reitores de Extensão das Universidades Públicas Brasileiras desde 1993. Atualmente, a avaliação das atividades de extensão representa um desafio para as universidades no sentido de definir critérios que possibilitem, pela avaliação interna, estabelecer princípios para nortear o processo de avaliação de extensão universitária. O fórum considera que a inclusão da extensão, como um dos parâmetros de avaliação da universidade, pressupõe considerar esta atividade como parte do fazer acadêmico que deve ser entendido como um processo orgânico e contínuo. E nessa perspectiva a extensão passa a ser entendida como um processo educativo, técnico e científico que articula o ensino e a pesquisa de forma indissociável e viabiliza a relação transformadora entre universidade e sociedade. Palavras-chave: Universidade; Extensão; Avaliação.